Konstruksi Hukum Tentang Kewajiban Perusahaan Daerah Bali Mempekerjakan Penyandang Disabilitas - Wirasningrum, Ketut Yulia (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 2 (2019), 2019)
Indonesia as a legal state must guarantee the human rights of all citizens, including persons with disabilities. Protection of the rights of persons with disabilities is regulated in international legal instruments as well as several national legal instruments. At the regional level, the Bali Provincial Government issued Bali Local Regulation Number 8 of 2015 concerning Protection and Fulfillment of the Rights of Persons with Disabilities. Regarding the rights to the employment of persons with disabilities in the Bali Regional Regulation there is a concept discrepancy with the provisions in the Disabled Persons Act regarding the percentage of disability employment in Regional Companies. Problems found include how the concept of the problem and the ideal legal regulatory solutions regarding the obligations of Bali Regional Companies to employ persons with disabilities. The purpose of this study is for the disability workforce to be absorbed maximally in the Regional and private companies. To obtain answers to these problems, normative research methods are used with conceptual approaches and regulatory approaches. Conclusions in this discussion that in Bali Regional Regulation Number 8 of 2015 concerning the protection and fulfillment of the rights of persons with disabilities there are still problems with corporate concepts that combine the concepts of Regional Companies and private companies. ideally in the future classification of company concept arrangements will be carried out so that the obligations of Regional and private companies in employing disability workers fulfill material values ??and formal legislation. Negara Indonesia sebagai negara hukum wajib menjamin hak asasi seluruh warga negara termasuk penyandang disabilitas. Perlindungan hak asasi penyandang disabilitas diatur dalam instrumen hukum Internasional serta beberapa instrument hukum nasional. Di tingkat daerah,  Pemerintah Provinsi Bali menerbitkan Perda Bali Nomor 8 Tahun 2015 tentang Perlindungan Dan Pemenuhan Hak Penyandang Disabilitas. Perihal hak atas pekerjaan penyandang disabilitas dalam Perda Bali terdapat ketidaksesuaian konsep dengan ketentuan dalam Undang-Undang Penyandang Disabilitas perihal persentase penerimaan tenaga kerja disabilitas pada Perusahaan Daerah. Masalah yang ditemukan antara lain bagaimana problem konsep serta solusi pengaturan hukum yang ideal perihal kewajiban Perusahaan Daerah Bali Mempekerjakan penyandang disabilitas. Tujuan dari penelitian ini agar tenaga kerja disabilitas dapat terserap dengan maksimal pada Perusahaan Daerah maupun swasta. Untuk memperoleh jawaban dari permasalahan tersebut digunakan metode penelitian normative dengan pendekatan konsep dan pendekatan peraturan perundang-undangan. Simpulan dalam pembahasan ini bahwa dalam Perda Bali Nomor 8 Tahun 2015 tentang perlindungan dan pemenuhan hak penyandang disabilitas masih terdapat masalah konsep perusahaan yang menggabungkan konsep Perusahaan Daerah dan perusahaan swasta. idealnya ke depan dilakukan klasifikasi pengaturan konsep perusahaan sehingga kewajiban Perusahaan Daerah dan swasta dalam mempekerjakan tenaga kerja disabilitas memenuhi nilai material dan formal peraturan perundang-undangan.